PENGARUH GAYA HIDUP, FITUR DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN OPPO SMARTPHONE DI KOTA PADANG - SEPRIANTO, SEPRIANTO (STIE Perbankan Indonesia, 2018)
The purpose of this study was to determine the effect of lifestyle, features and promotions on purchasing decisions Oppo Smartphone in Padang city. The population in this study were all consumer’s who buying product Oppo Smartphone in Padang city. The sampling technique was purposive sampling, while the number of samples for analysis were 80 consumer’s. Technique of data analysis for testing hypotheses is multiple linear regression.The results found that the lifestyle and promotions effect significan on purchasing decisions and features not significan effect on purchasing decisions. Contributions lifestyle, features and promotions on purchasing decisions Oppo Smartphone in Padang city is 38.3%.